Nurse Administrator Role for Emerging Infectious Diseases Nursing Service Management in hospital - Akathin, Sirinya (Journal of The Royal Thai Army Nurses, 2021)
Problems of the situation of the epidemic of Corona 2019 (COVID-19) many waves in Thailand. As a result, nursing administrators have to face various problems in managing nursing services. The work processes are adjusted in accordance with the epidemic situation of each new incidence. To achieve the effectiveness of the organization to success nursing administrators play an important role in the management of nursing services in emerging communicable disease situations, divided into 3 phases: 1) Pre-epidemic phase: 1.1) The role of management in the development of nursing knowledge 1.2) The role of building allocation planning and protective equipment 1.3) The role of assessment of operational readiness 2) During the epidemic period: 2.1) The role of communication and building relationships with the health team 2.2) The role of risk management 2.3) The role of staffing nursing team. 2.4) The role of building allocation 2.5) The role of information system management 2.6) The role of bed allocation management in hospital 3) Post-epidemic period 3.1) The role of management and evaluation of service outcomes 3.2) The role of nursing services development and improvement in preparation for the epidemic situation of Emerging Infectious Diseases in the future.